A case of survival following intake of a potentially lethal dose of enalapril. (1st October 2016) - Liu, Xiao-Wei; Jin, Yan; Liu, Zhi
Abstract: The report describes a successfully treated clinical case of the intoxication of a woman who ingested a potentially lethal dose of enalapril, complicated by profound hypotension and redundant pleural effusion. The patient ingested 700 10-mg enalapril tablets. The patient was admitted to the emergency room with obvious weakness and lethargy. High plasma levels of renin activity and low plasma levels of angiotensin II and aldosterone confirmed the diagnosis of life-threatening hypotension. Comprehensive therapy consisted of rapid intravenous infusion of fluids and plasma and the administration of dopamine and norepinephrine along with hemodialysis. The patient was successfully treated and made a full recovery.